Pengaruh Kinerja Karyawan terhadap Penjualan di Gerai Anyardrink Tanggul Serang-Banten - M Syaepudin; Herdiansah Herdiansah; Asifatunisa Asifatunisa; Amanda Jesica Loren; Riki Gana Suyatna (Journal of Management and Social Sciences, 2024)
The aim of this research is to determine the effect of employee performance on sales which is mediated by competitive advantage. This research was conducted on Anyardrink store employees with syrup products. There were 8 types/brands of syrup used with various flavors, using a non-probability method in the form of incidental and purposive sampling. The data analysis technique used is Path Analysis and sampling test. Based on the results of the analysis, it was found that the regression model used met the classical assumption test. This research found that 1) Entrepreneurial Orientation has a positive and significant effect on Competitive Advantage; 2) Competitive Advantage has a positive and significant effect on Marketing Performance; 3) Employee orientation has a positive and significant effect on Sales Performance; 4) Competitive Advantage is proven to positively and significantly mediate the influence of Entrepreneurial Orientation on Marketing Performance.